2009
DOI: 10.1097/ede.0b013e31819b93c0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Blood Manganese Levels and Infant Birth Weight

Abstract: Background Manganese is both an essential element and a known neurotoxicant to children. High manganese exposures have been associated with negative reproductive outcomes in animals, but few epidemiologic studies have examined the effects of human fetal manganese exposure. Methods We studied the association between maternal and umbilical cord blood manganese levels and birth weight in a cohort of 470 mother-infant pairs born at term (≥37 weeks gestation) in Ottawa County, Oklahoma. Nonlinear spline and quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
155
9
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(183 citation statements)
references
References 29 publications
17
155
9
2
Order By: Relevance
“…The mean age of the mothers was 29 years, the mean pre-pregnancy BMI was 23.1 kg/m 2 , the mean estimated gestational length was 39.7 weeks, 50% of women have at least university education, 53.8% of babies were males, and the mean birth length for all babies was 51.4 cm. The mean birth weight of the babies in our study was comparable with those reported elsewhere [23,30,35,38,45,46]. A total of 3.4% of the new-borns were below the criterion for "low birth weight" of 2,500 g [17], and 0.2% of new-borns were below 1,500 g, considered as a "very low birth weight" [47].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The mean age of the mothers was 29 years, the mean pre-pregnancy BMI was 23.1 kg/m 2 , the mean estimated gestational length was 39.7 weeks, 50% of women have at least university education, 53.8% of babies were males, and the mean birth length for all babies was 51.4 cm. The mean birth weight of the babies in our study was comparable with those reported elsewhere [23,30,35,38,45,46]. A total of 3.4% of the new-borns were below the criterion for "low birth weight" of 2,500 g [17], and 0.2% of new-borns were below 1,500 g, considered as a "very low birth weight" [47].…”
Section: Discussionsupporting
confidence: 72%
“…Mn is an important cofactor in enzyme reactions in bone formation and in metabolic regulation of levels of amino acid, lipid, protein and carbohydrate [25,27]. However, in contrast to the present study, only non-significant or non-linear correlations between birth weight and Mn have been reported [22,23,25,26].…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…A study by Vigeh et al, reported on the relationship between maternal blood Mn concentration and intrauterine growth restriction (IUGR) 4 . An inverted U-shape relationship between maternal blood Mn levels and infant birth weight has been shown by other 15 . A number of studies on neonates and infants have confirmed decreased elimination mechanisms for Mn, making neonates and infants receiving total parenteral nutrition or formulas containing Mn highly susceptible to Mn neurotoxicity [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 52%
“…15-20 µg/L) than the values observed in the blood of the general adult population (4-15 μg/L; see Section 2.3.2) (Takser et al, 2004;Rudge et al, 2009;Zota et al, 2009;Kopp et al, 2012). Studies in mother-child pairs report manganese concentrations in cord blood which are two-to three-fold higher (range of means: ~ 30-40 µg/L) than in maternal blood (Takser et al, 2003;Takser et al, 2004;Vigeh et al, 2008;Zota et al, 2009;Kopp et al, 2012).…”
Section: Distribution To Tissuesmentioning
confidence: 94%